EXPLORING MEDICINAL PLANT DIVERSITY: AN ETHNOBOTANICAL STUDY OF THE SIDANG MAS MALAY COMMUNITY IN BANYUASIN REGENCY - Syarifah Syarifah; Delia Yusfarani (Berita Biologi, 2026)
South Sumatra Province is one of the provinces with a diverse range of plants that can be used as traditional medicine. Research was conducted to explore medicinal plants in Sidang Emas Village, Banyuasin III District, Banyuasin Regency, South Sumatra Province. The people of Sidang Emas Village are part of the Malay community in South Sumatra. This study aims to analyze the ethnobotany of medicinal plants used by the Sidang Emas community, which has not been previously studied. Ethnobotanical exploration can reveal the use of traditional medicinal plants and their processing in curing diseases in Sidang Emas Village. The findings of the study showed 34 plant species from 25 different families that have been utilized as medicines. The phytochemical screening revealed that 33% of these plants contained alkaloids, 32% contained flavonoids, and 31% contained tannins; 4% contained phenols, and none contained saponins. It is correlated with the health benefits of plants, including the treatment of digestive problems, external wounds, shortness of breath, and blood sugar levels.